2014
DOI: 10.1016/j.cej.2014.05.097
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic effects of wool fibers modified with solely TiO2 nanoparticles and N-doped TiO2 nanoparticles by using hydrothermal method

Abstract: Abstract:The surfaces of wool fibers are modified with N-doped TiO2 nanoparticles by treating the fibers with tetrabutyl titanate and ammonium chloride under low temperature hydrothermal conditions to obtain wool fibers with photocatalytic functions in the visible light spectrum. The effects of nitrogen and sulfur in amino acids in keratin on the photocatalytic activity of TiO2 particle coated wool fibers are investigated. Changes of various fiber properties such as tensile strength, surface friction, photocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 56 publications
(46 reference statements)
0
20
0
Order By: Relevance
“…In the past few decades, considerable research studies have shown that doping TiO 2 with non-metal elements, such as carbon, boron, fluorine, nitrogen and sulphur, enables the realization of visible light-responsive TiO 2 . Among those studies, nitrogen doping has been proved to be a modest and most effective technique [15] to achieve visible light stimulated photocatalytic activities of TiO 2 . However, most of the studies on nitrogen-doped TiO 2 have assumed that the nitrogen doping results in a surface or sub-surface modification making it difficult to narrow down the band gap in the bulk of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, considerable research studies have shown that doping TiO 2 with non-metal elements, such as carbon, boron, fluorine, nitrogen and sulphur, enables the realization of visible light-responsive TiO 2 . Among those studies, nitrogen doping has been proved to be a modest and most effective technique [15] to achieve visible light stimulated photocatalytic activities of TiO 2 . However, most of the studies on nitrogen-doped TiO 2 have assumed that the nitrogen doping results in a surface or sub-surface modification making it difficult to narrow down the band gap in the bulk of TiO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained in this study motivated us to carry out experiments with other metal oxides such as titanium oxide. A study of the synthesis of titania in the presence of spongin-based scaffolds has not been reported before, but the immobilization of titania nanoparticles onto alternative proteinaceous substrates (e.g., wool or feather keratin) has been extensively studied [26,27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The optical absorption edge extends to visible light region owing to the coating of TiO 2 nanoparticles. It has been confi rmed that the co-doping of carbon, nitrogen, oxygen, and sulfur in the TiO 2 -modifi ed wool fi bers acts as a trapping center for electrons and holes, thereby reducing the recombination rate of charge carriers [49]. The relationship between (αhν) 2 and incident photon energy (hν) for the W2 specimens is shown in Figure 5, where α is the absorption coeffi cient.…”
Section: Optical Propertymentioning
confidence: 98%